ETIKA MENCARI PENDAMPING HIDUP MENURUT ISLAM - Zurifah Nurdin (JURNAL ILMIAH SYI'AR, 2017)
Life in pairs is a fitrah that is bestowed by the divine, and it is necessary to appreciate therefore in search of human companion and especially for Muslims it is good to use ethics. Ethics in seeking life companion is very important, so worth worship, so that household become sakinah, mawaddah and rohmah.